Brazilian Design Thinking: A systematic literature review of theses and dissertations (Estudos em Design, 2017)
This paper aims to analyze Brazilian theses and dissertations examining Design Thinking to provide an updated picture of how this strategic element has been used in the academic postgraduate perspective in Brazil. A systematic literature review was performed using the Capes website, since it is the official Brazilian online database of theses and dissertations. The result is 65 studies that meet the selection criteria of having the term “Design Thinking” or “Design Thinker” in the research title, abstract or keywords and were published up to December of 2016. The results show that Brazilian DT research is concentrated in few institutions and focused almost entirely on one DT concept.